we conclude that the problem is in step 2, and the real solution of the expression is 44.
We have the expression:
2*(10 - 6)^2 + 3*4
The first step is simplifying the subtraction in the left term, so we get:
2*(10 - 6)^2 + 3*4 = 2*(4)^2 + 3*4
Now, in the next step what your friend does is taking the product:
2*(4)^2 = 8^2
This is wrong, you can't distribute the exponent, so what you need to do here is:
2*(4)^2 = 2*16 = 32
Replacing that in our operation:
2*(4)^2 + 3*4 = 32 + 3*4 = 32 + 12 = 44
Finally, we conclude that the problem is in step 2, and the real solution of the expression is 44.
If you want to learn more about exponents:
https://brainly.com/question/11464095
#SPJ1